Sine Integration

Calculus Level 5

0 π sin 4 ( x + sin ( 3 x ) ) d x \large\displaystyle\int_0^\pi\sin^4(x+\sin(3x))\, dx

If the integral above equals to a π b \dfrac{a\pi}b , where a a and b b are coprime positive integers, find a + b a+b .


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Jack Lam
Jul 7, 2016

Relevant wiki: Integration of Trigonometric Functions - Intermediate

Identity 1:

8 sin 4 θ cos 4 θ 4 cos 2 θ + 3 8\sin^4{\theta} \equiv \cos{4\theta} - 4\cos{2\theta} + 3

Proof:

2 i sin θ e i x e i x 2i\sin{\theta} \equiv e^{ix} - e^{-ix}

( 2 i sin θ ) 4 e 4 i x + e 4 i x 4 ( e 2 i x + e 2 i x ) + 6 (2i\sin{\theta})^4 \equiv e^{4ix} + e^{-4ix} - 4(e^{2ix} + e^{-2ix}) + 6

16 sin 4 θ 2 cos 4 θ 8 cos 2 θ + 6 16\sin^4{\theta} \equiv 2\cos{4\theta} - 8\cos{2\theta} + 6

8 sin 4 θ cos 4 θ 4 cos 2 θ + 3 8\sin^4{\theta} \equiv \cos{4\theta} - 4\cos{2\theta} + 3

Identity 2:

cos θ cos ( θ + π 3 ) cos ( θ π 3 ) 0 \cos{\theta} - \cos{(\theta + \frac{\pi}{3})} - \cos{(\theta - \frac{\pi}{3})} \equiv 0

Proof:

LHS cos θ ( 2 cos θ cos π 3 ) (by Sums to Products) \text{LHS} \equiv \cos{\theta} - (2\cos{\theta}\cos{\frac{\pi}{3}}) \text{(by Sums to Products)}

LHS cos θ cos θ 0 RHS \text{LHS} \equiv \cos{\theta} - \cos{\theta} \equiv 0 \equiv \text{RHS}

Now, let the integral in question be I I .

Then from Identity 1, 8 I = 0 π cos ( 4 x + 4 sin 3 x ) 4 cos ( 2 x + 2 sin 3 x ) + 3 d x 8I = \int_0^\pi \cos{(4x + 4\sin{3x})} - 4\cos{(2x + 2\sin{3x})} + 3 \, \text{d}x

Break off the constant term and evaluate it directly to obtain

8 I = 3 π + J 8I = 3\pi + J

Where J = 0 π cos ( 4 x + 4 sin 3 x ) 4 cos ( 2 x + 2 sin 3 x ) d x J = \int_0^\pi \cos{(4x + 4\sin{3x})} - 4\cos{(2x + 2\sin{3x})} \, \text{d}x

Use the standard border flip or substitute u = π x u = \pi-x and we have

J = 0 π cos ( 4 x 4 sin 3 x ) 4 cos ( 2 x 2 sin 3 x ) d x J = \int_0^\pi \cos{(4x - 4\sin{3x})} - 4\cos{(2x - 2\sin{3x})} \, \text{d}x

Add these two together and by direct expansion or Sums to Products, we obtain

J = 0 π cos 4 x cos ( sin 3 x ) 4 cos 2 x cos ( 2 sin 3 x ) d x J = \int_0^\pi \cos{4x}\cos{(\sin{3x})} - 4\cos{2x}\cos{(2\sin{3x})} \, \text{d}x

Break up J J along the three intervals: { 0 , π 3 } , { π 3 , 2 π 3 } , { 2 π 3 , π } \{0,\frac{\pi}{3}\} , \{\frac{\pi}{3},\frac{2\pi}{3}\} , \{\frac{2\pi}{3},\pi\}

Leave the first interval alone.

For the second interval, substitute u = x π 3 u = x-\frac{\pi}{3}

J 2 = 0 π 3 cos ( 4 u + 4 π 3 ) cos ( 4 sin ( 3 u + π ) ) 4 cos ( 2 u + 2 π 3 ) cos ( 2 sin ( 3 u + π ) ) d x J_2 = \int_0^\frac{\pi}{3} \cos{(4u+\frac{4\pi}{3})} \cos{(4\sin{(3u + \pi)})} - 4\cos{(2u+\frac{2\pi}{3})} \cos{(2\sin{(3u+\pi)})} \, \text{d}x

J 2 = 0 π 3 cos ( 4 x + π 3 ) cos ( 4 sin 3 x ) 4 cos ( 2 x π 3 ) cos ( 2 sin 3 x ) d x J_2 = -\int_0^\frac{\pi}{3} \cos{(4x+\frac{\pi}{3})}\cos{(4\sin{3x})} - 4\cos{(2x-\frac{\pi}{3})}\cos{(2\sin{3x})} \, \text{d}x

For the third interval, substitute u = x 2 π 3 u = x-\frac{2\pi}{3}

J 3 = 0 π 3 cos ( 4 u + 8 π 3 ) cos ( 4 sin ( 3 u + 2 π ) ) 4 cos ( 2 u + 4 π 3 ) cos ( 2 sin ( 3 u + 2 π ) ) d x J_3 = \int_0^\frac{\pi}{3} \cos{(4u+\frac{8\pi}{3})} \cos{(4\sin{(3u + 2\pi)})} - 4\cos{(2u+\frac{4\pi}{3})} \cos{(2\sin{(3u+2\pi)})} \, \text{d}x

J 3 = 0 π 3 cos ( 4 x π 3 ) cos ( 4 sin 3 x ) 4 cos ( 2 x + π 3 ) cos ( 2 sin 3 x ) d x J_3 = -\int_0^\frac{\pi}{3} \cos{(4x-\frac{\pi}{3})}\cos{(4\sin{3x})} - 4\cos{(2x+\frac{\pi}{3})}\cos{(2\sin{3x})} \, \text{d}x

Adding up all three pieces of the integral together and using Identity 2, we find at last that J = 0 J = 0

Hence, 8 I = 3 π 8I = 3\pi

And finally, we have a + b = 3 + 8 = 11 a+b = 3+8 = 11

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...